Executive Information System Berbasis Scrum untuk Monitoring dan Visualisasi Penyebaran Demam Berdarah Dengue (DBD) - Rohmah, Sefia Nur; Trivilia, Indah; Khumaida, Rizka; Setiawan, Retno Agus (Universitas Harapan Bangsa, 2025)
The Executive Information System (EIS) is designed to provide strategic reports that assist executives in making decisions quickly, accurately, and based on data. In the context of public health, the EIS plays a vital role in monitoring and controlling the spread of vector-borne infectious diseases such as Dengue Hemorrhagic Fever (DHF). This study aims to design and develop an initial web-based prototype of an EIS capable of detecting and monitoring the spread of DHF in Indonesia through interactive data visualization, statistical analysis, and informative geographic mapping. The system development adopted the Scrum approach, consisting of several stages: product backlog, sprint planning, daily scrum, sprint review, and sprint retrospective. The results indicate that all sprints were completed on schedule, producing a prototype that displays case distribution data, temporal trends, and high-risk areas equipped with features such as filtering, drill-down analysis, and data importing. However, this study remains at the initial design stage; therefore, user validation testing has not yet been conducted. This stage is planned for future research through Usability Testing (System Usability Scale) and Decision-Making Effectiveness Evaluation to assess the level of user acceptance, ease of use, and the system’s impact on executive decision-making in the field of public health.